2015
DOI: 10.15763/issn.2376-5275.2015.1.1.1-45
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Methods Study of Pre-­service Teachers’ Attitudes toward LGBTQ Themed Literature

Abstract: <p>While many of studies provide valuable insights into teachers’ attitudes toward LGBTQ curricula, more research is needed that examines pre-service teachers’ attitudes toward LGBTQ themed texts.  The results from the type of research reported on in this article could assist teacher preparation programs to develop coursework intended to increase the willingness of pre-service teachers to use LGBTQ themed young adult literature in the classroom. </p>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…al., 2012). These beliefs were verified by numerous researchers who have found both student teachers and permanent classroom teachers to feel uncomfortable and/or unprepared to confront homophobia (Haertling-Thein, 2013;Malo-Juvera, 2015;Meyer, 2008;Zack, Mannheim, & Alfano, 2010). Some scholars contend that schools are homophobic institutions (Blackburn, 2004;Owens, 1998), while others even argue that educators condone homophobia and homophobic bullying (Rivers, 1995).…”
Section: Malo-juveramentioning
confidence: 94%
See 1 more Smart Citation
“…al., 2012). These beliefs were verified by numerous researchers who have found both student teachers and permanent classroom teachers to feel uncomfortable and/or unprepared to confront homophobia (Haertling-Thein, 2013;Malo-Juvera, 2015;Meyer, 2008;Zack, Mannheim, & Alfano, 2010). Some scholars contend that schools are homophobic institutions (Blackburn, 2004;Owens, 1998), while others even argue that educators condone homophobia and homophobic bullying (Rivers, 1995).…”
Section: Malo-juveramentioning
confidence: 94%
“…Considering that researchers (Haertling-Thein, 2013;Malo-Juvera, 2015) have found that many preservice and inservice teachers are reluctant to use LGBTQ themed literature, this study could be used as part of teacher education and professional development as a strong justification to the reticent/unwilling about the benefits of using LGBTQ texts. Furthermore, because Malo-Juvera (2015) found that preservice English teachers felt unprepared to lead discussions about LGBTQ topics, the success of this study argues there is a need to introduce preservice and inservice teachers to dialogic instruction, especially when dealing with issues that some may find controversial.…”
Section: Implications For Teachingmentioning
confidence: 99%
“…Falter (2016) used YAL in a teacher education course to help PSTs reflect on and revise their negative assumptions and stereotypes about adolescent learners. Others have used YAL in teacher preparation to facilitate discussions of and learning about issues such as bullying and suicide (Pytash, 2013), race (Glenn, 2012), perspective recognition and empathetic reading (Cook et al , 2017), queer pedagogies (Bach, 2016), LGBTQ literature (Greathouse and Diccio, 2016; Malo-Juvera, 2015), social justice teaching and positionalities (Cook and Bissonnette, 2016; Glasgow, 2001), global perspectives on diversity (Duran, 2015), death and dying (Sams and Cook, 2018), and so forth. TEs have also used YAL in self-studies of their teacher preparation programs and courses (Parsons, 2006) and to critically reflect on their own teaching (Miller, 2008).…”
Section: Young Adult Literature and Teacher Educationmentioning
confidence: 99%
“…However, applications of QFA need not involve data collected through Q-sorting. Instead, in QFA, data can be collected through various sources such as interviews and surveys (Malo-Juvera, 2015; Yang and Bliss, 2014) with the goal in all cases being to identify typologies of people.…”
Section: Introductionmentioning
confidence: 99%